THE IMPLEMENTATION OF DIARY WRITING IN TEACHING WRITING RECOUNT TEXT FOR TENTH GRADE STUDENTS - yusridanova, ivana wuri (RETAIN, 2021)
Abstract Diary writing is known to function as one of the ways in leading the students to constantly write since it should a lot more interesting. It takes a lot of practice to make their writing skill better. A. Hanan et al. (2015) claimed that writing a diary is known as a daily basis activity of writing in which it records all kinds of activities in one day. It is known that a diary is privately written by the author. In that case, there are lots of benefits that teachers will get when they start to use diary writing in a classroom. Due to that issue, the researcher finally conducted a research in which it covers how diary writing was implemented to teach tenth graders in writing recount text, how students performed their writing skill during diary writing’s implementation, and also how students responded to the diary writing’s implementation. To get the data, some steps were done by the researcher to get the findings which it started with by observing and analyzing the teaching and learning process using the observational sheet. Then the researcher collected the transcription of the dialogues extracted from the talk between students and the teacher, and the talk among students by using field notes. Moreover, to justify students’ writing ability, the researcher judged and analyzed students’ compositions of writing recount text by deeply exploring into the aspect of content, language use, organization, vocabulary, and mechanics. Finally, to know how the students responded to the existence of diary writing in the classroom, the researcher conducted an interview. Here, the findings showed that: first of all the diary writing's implementation went to some sort stages of introducing what recount text is, demonstrating how to produce a good paragraph and finally showing the steps in writing a diary; secondly, almost half of the students were considered to be good writers of dairy while the rest needed more practice; and lastly half of the students were showing positive reaction towards the implementation of diary writing. Keywords: diary writing, writing skill, recount text.